Ilmu dan Islam: Mengurai Konsep dan Sumber Ilmu dalam Al-Qur’an dan Hadis - Fadli Rahman; Mahyuddin Barni (IAIN Palangka Raya, 2021)
This study aims to explore the meaning or concept of the word “knowledge” often mentioned in the Quran and Hadith. The first step was by taking an inventory of the verses that talk about knowledge and then categorizing them thematically. The data obtained were then analyzed with the descriptive-analytical method. It resulted in three findings. First, the verses related to knowledge in the Quran and Hadith are still general and need interpretation to understand the essential meaning related to the definition or nature of knowledge conceptually. Second, there are three components in acquiring knowledge, namely the senses, reason, and inspiration. Third, interpretation gives birth to different opinions on the sources of knowledge, especially between Al-Ghazali and his rivals. These differences are caused by different perspectives in interpreting the verses of the Qur'an and Hadith. Keywords: Source of knowledge; The concept of knowledge; Knowledge in the Quran; Knowledge in the Hadith